2023
DOI: 10.3390/diseases11010027
|View full text |Cite
|
Sign up to set email alerts
|

“To Be or Not to Be Benign” at Partial Nephrectomy for Presumed RCC Renal Masses: Single-Center Experience with 195 Consecutive Patients

Abstract: In daily medical practice, an increasing number of kidney masses are being incidentally detected using common imaging techniques, owing to the improved diagnostic accuracy and increasingly frequent use of these techniques. As a consequence, the rate of detection of smaller lesions is increasing considerably. According to certain studies, following surgical treatment, up to 27% of small enhancing renal masses are identified as benign tumors at the final pathological examination. This high rate of benign tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Several studies conducted on young adults reported similar results regarding the types of benign lesions (23,24,26). The diagnosis of RCC and the decision for surgery primarily depended on radiological imaging methods.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies conducted on young adults reported similar results regarding the types of benign lesions (23,24,26). The diagnosis of RCC and the decision for surgery primarily depended on radiological imaging methods.…”
Section: Discussionmentioning
confidence: 82%
“…In most cases, these radiological imaging methods successfully diagnosed RCC, but occasionally they faced challenges in differentiating oncocytoma and lipid-poor AML from RCC (12)(13)(14). In the general population, the detection rate of benign tumors in patients who had surgery for RCC was reported as being around 11-16% (23)(24)(25). Aslan et al conducted a study evaluating localized renal masses in patients aged <40 years, and reported that 24% of the patients were diagnosed with benign lesions (26).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of PN makes it possible to reduce the risk of performing radical surgery (with the consequent removal of the kidney) in the case of benign neoplasia, although the latter may have larger diameters. With respect to this, in our previous research [19], the medical records of patients undergoing laparoscopic PN at our department over the last 10 years were retrospectively reviewed, including a total of 195 patients. The analysis result was that 30 (15.4%) of the 195 kidney lesions removed were diagnosed as benign by the pathologist, with a complication rate of 10% (3/30 cases) among these patients.…”
Section: Introductionmentioning
confidence: 99%